Modernization and Cultural Identity in Contemporary China - Yang, Suhuai; Song, Chao; Kwan, Hongmei; Zhang, Wei (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Over the past four decades, China has undergone a rapid and comprehensive modernization process, transforming the country's economic, social, and cultural structures. This transformation reflects not only economic growth and technological innovation but also tensions between tradition and modernity in cultural identity. This study highlights how modernization shapes the cultural identities of China's urban youth through a qualitative approach, combining digital discourse analysis and in-depth interviews. Furthermore, it examines China's civilizational diplomacy as a global strategy that combines cultural hegemony, soft power, and epistemic challenges to the Western order. Using the A-DUNK framework, the study identifies three main findings: first, civilizational diplomacy displays a duality between inclusive dialogue and the centrality of Cynical morality; second, China's soft power is built through moral legitimacy that emphasizes historical continuity and civilizing values; and third, this diplomacy presents epistemic challenges that emphasize relationality and coexistence among civilizations. The discussion shows that China's approach aligns with civilizational pluralism, yet still faces tensions between inclusive rhetoric and asymmetrical practices. Normatively, the success of China's civilizational diplomacy hinges on its ability to institutionalize ethical reciprocity, transforming moral discourse into an inclusive procedural mechanism. This study contributes to an interdisciplinary understanding of Chinese modernization and diplomacy as phenomena that are not only geopolitical but also normative and epistemic, offering a model of